Digital disruption of optimal co-innovation configurations - Lafuente, Esteban; Vaillant, Yancy; Rabetino, Rodrigo (Elsevier, 2023)
We evaluate the co-innovation trajectory of firms adopting different collaborative innovation networks (i.e., vertical, horizontal, and institutional). The results of the empirical applications are obtained from a multilevel regression, and a Nash bargaining model estimated via data envelopment analysis on a sample of 734 enterprises from seven OECD countries form Europe and Latin America. Findings point to important national and firm-level distinctions across the optimal co-innovation configurations: whereas vertical co-innovation strategies are characteristic of firms with the highest innovation efficiency, institutions are frequently found to be optimal for co-innovation success in less developed innovation systems that may be faced with structural deficiencies. However, digital competency is found to disrupt co-innovation configurations for successful innovation, facilitating the development of efficient vertical and horizontal co-innovation trajectories.
Keywords: Co-innovation; Nash bargaining model; Business networks; Ecosystems; Digital technologies; Configurations; Data envelopment analysis; Multilevel; International; fi=Strateginen johtaminen|en=Strategic Management|